A vicious cycle of superficial conceptualization: Deconstructing nature in social innovation (policy) discourse - Ergun, Hande Sinem; Samur-Teraman, Seray Begüm (NOvation — Critical Studies of Innovation, 2023)
Critical studies of social innovation (SI) reveal sustainability concepts are widely used by scholars, policy makers and practitioners on a superficial level (Eichler & Schwarz, 2019). Even if SI is mainly linked to social and economic dimensions, the relationship between SI and environment is still vague and needs further research. One possible reason for this disconnectedness would be the dominating anthropocentric assumptions instead of ecocentric assumptions? To fill this gap, this paper aims to explore the conceptualization of nature in SI documents. We do this through an analysis of United Nations (UN) publications, particularly, United Nations Development Programme (UNDP) Accelerator Labs. In addition, we consider how SI is understood, executed, promoted and how perceptions of nature affect SI. Eco-critical discourse analysis (ECDA) is adopted as an analytical approach for this study. This study utilizes texts as empirical material on SI published by the UN. The focus on the UN is appropriate, as they are a highly influential institution on national economies in shaping their SI policies and practices. Therefore, this study is undertaken on the basis that the discourse of these documents affects the SI discourse and practices of countries and the field. The contribution of this study lies in its effort to reveal embedded propositions in SI texts through language-driven analysis, then to discuss how a deeper understanding would regain the agenda for long-lasting socio-economic problems through an ecocentric critical discourse.